2022
DOI: 10.1108/apjba-11-2021-0579
|View full text |Cite
|
Sign up to set email alerts
|

Emotional attachment: a bridge between brand reputation and brand advocacy

Abstract: PurposeThis study aims to identify and examine the effect of brand reputation on brand advocacy by evaluating the mediating effect of emotional attachment. The study also tests the relationships by appraising the moderating effect of experience and price perception. The research model is also assessed across the two brand types (hedonic brands and utilitarian brands).Design/methodology/approachOverall, 426 valid questionnaires were collected through an online survey. To test the proposed hypotheses, structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 81 publications
4
12
0
Order By: Relevance
“…A similar finding has been reported in the study conducted by Chen et al (2006). Consumers develop strong emotional attachment with favourable brands (Ahmadi and Ataei, 2022). Based on above, the following hypotheses were proposed:…”
Section: Reputationsupporting
confidence: 74%
See 1 more Smart Citation
“…A similar finding has been reported in the study conducted by Chen et al (2006). Consumers develop strong emotional attachment with favourable brands (Ahmadi and Ataei, 2022). Based on above, the following hypotheses were proposed:…”
Section: Reputationsupporting
confidence: 74%
“…Literature highlights that the alumni with high attachment strength are likely to donate more to the HEIs in comparison to the alumni who do not find themselves attached to the institution (Bae and Kim, 2018). Furthermore, students as brand advocates are the most effective and least costly promotional tool (Ahmadi and Ataei, 2022). Individual's (student's) actions, behaviours and cognitive representations are inherently shaped by mental representation of attachment figure (institute).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they may protect credibility for their brand, which eventually turns into brand advocacy. Brand advocacy not only maximizes the level of approval of the relationship between the consumer and the brand but might leave positive reviews about the brand or product of an organization (Ahmadi and Ataei, 2022). Apart from brand advocacy, this study found that brand credibility could encourage mindful consumption behavior, reflecting a desire for avoiding overconsumption.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer behavior research has repeatedly demonstrated the mediating role that such constructs play, including brand attachment (Ahmadi & Ataei, 2022;Japutra et al, 2019;Li et al, 2020); psychological empowerment (Han et al, 2019;Yoo, 2017); and customer brand engagement (Harrigan et al, 2020;Naeem & Ozuem, 2021).…”
Section: Customer Brand Engagement and Brand Advocacymentioning
confidence: 99%